Referral Acceptance System For Patients With Non-Communicable Diseases Of The Elderly In The Tough Doctor Program To Rsud Haji Abdoel Madjid Batoe - Taqwin, Ahmad; Kidrawati, Atik; Nurhayati, Nurhayati; Agustin, Dinni (Journal of Ageing And Family, 2024)
Non-communicable diseases are chronic illnesses such as hypertension, diabetes mellitus, heart disease, and stroke. This study aims to analyze the challenges in the referral acceptance system for elderly NCD patients within the Tangguh Doctor Program at RSUD Haji Abdoel Madjid Batoe. This qualitative research was conducted at RSUD Haji Abdoel Madjid Batoe. The informants consisted of the Acting Head of the Batang Hari District Health Office, Sub-coordinator of Primary Health Services, representatives from BPJSKesehatan Batang Hari, representatives from RSUD Haji Abdoel Madjid Batoe, representatives from Bapperida of Batang Hari Regency, elderly NCD patients, Doctors (Tangguh Doctor Team), and staff of the TPPRJ at RSUD Haji Abdoel Madjid Batoe. Data collection used document review, in-depth interviews, and FGDs. The research findings indicate that each region has 1 Tangguh Doctor Team. The funding (Money) comes from APBD. Materials include stationery, medical devices, proof sheets and visit logbooks, visit registration books, and referral sheets. There is an existing SOP (Method). The equipment (Machine) includes a vehicle, but laptops/tablets and the Integrated Referral Information System (SISRUTE) are not yet available. The target (Market) is elderly patients with NCDs. The process involves the doctor determining the need for referral, the team taking the patient to the primary health center (puskesmas), and ensuring the patient receives care. The system's output issuboptimal, impacting efficiency and effectiveness. The primary cause is the team's lack of SISRUTE integration with P-Care for printing referrals. The main recommendation is the development of SISRUTE for Tangguh Doctors. Referral acceptance to RSUD Hamba is suboptimal due to the absence of SISRUTE- P-Care integration. It is suggested to develop a digital referral application to eliminate the need for patients to visit the primary health center for referral letters. This application should be connected with P-Care BPJS and SISRUTE. Keywords: System, Referral, Non-Communicable Diseases, Elderly